Incorporating critical thinking: teaching strategies in English language programme / Muhammad Harriz Zaini - Zaini, Muhammad Harriz (2015)
Critical thinking plays an important role in improving the quality of students and education all over the world. However, educators are criticized for not preparing students effectively for future employment since the students lacked critical thinking skills. Thus, educators need to be able to provide critical thinking learning environment in the classroom. This study focuses on the critical thinking application in the classroom for the English language programme in APB UiTM Shah Alam. This study aims to investigate how the English lecturers in APB perceive their critical thinking application in class as well as how their students perceive their critical thinking application in class. Additionally, the study investigates whether there is a significant difference between their perceptions regarding the critical thinking application in class. The study adapts a framework which introduced seven dimensions of critical thinking. A quantitative approach is employed in this study while questionnaires are used as instruments for collecting the data. A pilot test was conducted in order to measure the reliability as well as the validity of the instrument. From the findings, there is only one dimension that has a significant difference between the lecturers’ and the students’ perception of application in class. From this study, it can be concluded that both lecturers and students in APB are aware of the importance in incorporating critical thinking in learning and the current practice of critical thinking application should continue. Recommendations for future research are provided in the final chapter.